3D printing, debinding and sintering of stainless steel metamaterials via lithography metal manufacturing: processing, microstructure and properties relationships - Ruslan Melentiev; Ahmed Wagih; Gilles Lubineau; Carlos A. Grande (Materials & Design, 2025)
Sinter-based additive manufacturing (AM) technology via material extrusion, binder jetting, and lithography metal manufacturing (LMM) are well established methods in the three-dimensional printing ecosystem. Although the printing stage of sinter-based AM is well understood, the consolidation stage to dense metallic parts is currently a bottleneck for this type of technology. This study focuses on crackless debinding and defectless sintering of complex thin-walled structures, such as lattices and metamaterials. The effects of debinding and sintering conditions on the shape, density, microstructure, mechanical, thermal, and electrical properties of 316L stainless steel parts printed via LMM are investigated. We found that crackless debinding can be achieved 10 times faster when introducing a high-temperature preconditioning step and defined sintering temperature thresholds for rapid densification and grain development of the printed 316L steel lattices, yielding mechanical, thermal, and electrical properties comparable to those of rolled stainless steel.